A preliminary theory of dark network resilience - Bakker, René M.; Raab, Jörg; Milward, H. Brinton (Journal of policy analysis and management, 2012)
A crucial contemporary policy question for governments across the globe is how to cope with international crime and terrorist networks. Many such "dark" networks—that is, networks that operate covertly and illegally—display a remarkable level of resilience when faced with shocks and attacks. Based on an in-depth study of three cases (MK, the armed wing of the African National Congress in South Africa during apartheid; FARC, the Marxist guerrilla movement in Colombia; and the Liberation Tigers of Tamil Eelam, LTTE, in Sn Lanka), we present a set of propositions to outline how shocks impact dark network charactenstics (resources and legitimacy) and networked capabilities (replacing actors, linkages, balancing integration and differentiation) and how these in turn affect a dark network's resilience over time. We discuss the implications of our findings for policymakers.